Formation and strengthening mechanisms of xonotlite in C3S-silica and C2S-silica powder systems under high temperature and pressure. (July 2022) - Wei, Tingcong; Wei, Fengqi; Zhou, Jinghong; Wu, Zhiqiang; Zhang, Chunmei; Zhuang, Jia; Cheng, Xiaowei
Abstract: As oil and gas exploration advances into more complex underground formations, oil-well cement, used to support bore casings, is at risk of mechanical failure. To clarify the strengthening mechanisms of silica powder, the hydration characteristics of C3 S-silica and C2 S-silica powder systems were studied at high temperature (230 °C) and pressure (20.7 MPa). The results show that microstructural coarsening is the primary reason for the poor mechanical properties of the cementitious materials. The formation of xonotlite included two sources: the crystallisation reaction of silica powder with C-S-H and the pozzolanic reaction of silica powder with calcium hydroxide. The CaO layer in C-S-H and calcium hydroxide provided a 'Ca' source for the formation of xonotlite. Q 2 and Q 3 Si units with a high polymerisation degree improve the high-temperature stability of xonotlite, while the dense structure formed by xonotlite improves the mechanical properties. For designing high-performance high-temperature resistant cement-based materials, xonotlite should preferably be generated by selecting crystalline silica powder.